(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article describes general social background of contemporary publicity determined by mass culture. Conscious human apprehension of the world is formed not only by language, but also by daily experience and mass school education. Level of quality of an individual’s culture corresponds to the level of the society’s spiritual development.